Immune Response in Neurological Pathology: Emerging Role of Central and Peripheral Immune Crosstalk - Passaro, Austin P.; Lebos, Abraham L.; Yao, Yao; Stice, Steven L. (Frontiers in Immunology, 2021)
Neuroinflammation is a key component of neurological disorders and is an important therapeutic target; however, immunotherapies have been largely unsuccessful. In cases where these therapies have succeeded, particularly multiple sclerosis, they have primarily focused on one aspect of the disease and leave room for improvement. More recently, the impact of the peripheral immune system is being recognized, since it has become evident that the central nervous system is not immune-privileged, as once thought. In this review, we highlight key interactions between central and peripheral immune cells in neurological disorders. While traditional approaches have examined these systems separately, the immune responses and processes in neurological disorders consist of substantial crosstalk between cells of the central and peripheral immune systems. Here, we provide an overview of major immune effector cells and the role of the blood-brain barrier in regard to neurological disorders and provide examples of this crosstalk in various disorders, including stroke and traumatic brain injury, multiple sclerosis, neurodegenerative diseases, and brain cancer. Finally, we propose targeting central-peripheral immune interactions as a potential improved therapeutic strategy to overcome failures in clinical translation.